The Effect of Pentoxifylline on Radiobiological Parameters in the Rat Radiation Myelopathy - Kim, Won Dong; Park, Woo Yoon (Cancer research and treatment, 2006)
There is great recent interest in the potential value of using pentoxifylline (3,7-dimethyl-1(5-oxyhexyl)-xanthine, PTX) as an inhibitor of radiation-induced late normal tissue damage. The effects of PTX on the radiobiological parameters (alpha/beta ratio, repair half time T(1/2)) of radiation myelopathy were studied in a rat model. Anesthetized Sprague-Dawley rats received irradiation to 2 cm of their cervical spines with using a 6MV LINAC (dose rate: 3 Gy/min). Radiation was administered in single, two, four and eight fractions with a fraction interval of 24 h with or without PTX. PTX was added to the rats' distilled drinking water at a concentration of 2 g/L; the water was consumed ad libitum. After tabulation of the ED(50) (the estimated dose needed to produce 50% paralysis in a group of irradiated animals), alpha/beta could be estimated from the ratio of the slope to the intercept of the reciprocal-dose plot. Subsequently, the repair half time T(1/2) was obtained from the data of the experimental group that received a pair of 7 Gy fractions on each day, separated by intervals of 4 and 8 h. The alpha values calculated for RT alone and RT+ PTX were almost the same. We noticed that the beta value for the RT+PTX was lower than that for RT alone. So, the alpha/beta ratio for the RT+PTX was higher. The T(1/2) obtained from monoexponential model was 3.27 and 2.58 h for RT alone and RT+PTX, respectively. PTX increased the alpha/beta ratio and it decreased the T(1/2) of radiation myelopathy, suggesting that a decreasing fractionation sensitivity occurred. This implies that PTX, which distinctly acts upon the bending region of the high dose, may be expected to protect the spinal cord with a larger fraction size.